2002
DOI: 10.1097/00005392-200207000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow, Pressure and Compliance in the Male Human Bladder

Abstract: Human bladder blood flow tends to increase with increasing volume and pressure, and depends largely on local regulation. At capacity bladder blood flow is significantly decreased. Immediately after bladder drainage there is a rebound in blood flow, allowing reperfusion to occur. Decreased bladder blood flow and decreased bladder wall compliance correlated strongly, suggesting that ischemia may lead to structural changes in the bladder wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 28 publications
5
64
0
4
Order By: Relevance
“…LUTS were classified according to the IPSS as minimal (score 0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe ( > 20). The duration of LUTS was also recorded .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LUTS were classified according to the IPSS as minimal (score 0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe ( > 20). The duration of LUTS was also recorded .…”
Section: Methodsmentioning
confidence: 99%
“…However, in vitro models were developed, and strips of detrusor smooth muscle used to investigate how BOO affects detrusor physiology [9]. Recently, with the use of laser Doppler ultrasonography (US), bladder blood flow was found to decrease during the later stages of filling, along with the increase in intravesical pressure [11]. Thus we investigated the tissue distribution of ischaemia in human detrusor of patients with BOO, and correlated the results with clinical variables.…”
Section: Introductionmentioning
confidence: 99%
“…When filled with fluid, the distended bladder can enlarge to 15 times its decompressed volume, 33,34 reaching a capacity of approximately 400 cc or more. 35 Visually, distention leads to an apparent thinning of the layers.…”
Section: 31mentioning
confidence: 99%
“…Greenland Je et al [33] and Kershen et al [34] studied in pig and human respectively and concluded that blood flow in bladder reduces with distension that leads to detrusor ischemia and its impaired function. It has been shown in animal model that after reliving the obstruction, these changes are reversible as muscle mass returns to near normal, sensation and compliance improves and bladder capacity decreases.…”
Section: Neurological Diseasementioning
confidence: 99%
“…Many studies reveal that the duration of symptoms has adverse effect on bladder function as the long term bladder distension leads to irreversible ultrastructural changes in detrusor muscle and bladder wall but at what time period these irreversible changes occur, it is not clearly defined. Kershen RT [34] and Ohnishi N et al [37] postulated that long term distension of bladder leads to DM ischemia which leads to decrease bladder contractility and impaired bladder emptying causing CUR.…”
Section: Neurological Diseasementioning
confidence: 99%